Evaluation of an Innovative Colon Capsule Endoscopy Service in Scotland From the Perspective of Patients: Mixed Methods Study - Sarah Bond; Charalampos Kyfonidis; Matthew Jamieson; Roma Maguire; Lisa McCann; Angus Watson; Michelle Brogan; Marilyn Lennon (JMIR Publications, 2023)
BackgroundColonoscopy is the gold standard for lower gastrointestinal diagnostics. The procedure is invasive, and its demand is high, resulting in long waiting times. Colon capsule endoscopy (CCE) is a procedure that uses a video capsule to investigate the colon, meaning that it can be carried out in a person's own home. This type of "hospital-at-home" service could potentially reduce costs and waiting times, and increase patient satisfaction. Little is currently understood, however, about how CCE is actually experienced and accepted by patients. ObjectiveThe aim of this study was to capture and report patient experiences of the CCE technology (the capsule and associated belt and recorder) and of the new clinical pathway for the CCE service being rolled out as part of routine service in Scotland. MethodsThis was a mixed methods service evaluation of patient experiences of a real-world, deployed, managed service for CCE in Scotland. Two hundred and nine patients provided feedback via a survey about their experiences of the CCE service. Eighteen of these patients took part in a further telephone interview to capture more in-depth lived experiences to understand the barriers and opportunities for the further adoption and scaling up of the CCE service in a way that supports the patient experience and journey. ResultsPatients overall perceived the CCE service to be of significant value (eg, mentioning reduced travel times, reduced waiting times, and freedom to complete the procedure at home as perceived benefits). Our findings also highlighted the importance of clear and accessible information (eg, what to expect and how to undertake the bowel preparation) and the need for managing expectations of patients (eg, being clear about when results will be received and what happens if a further colonoscopy is required). ConclusionsThe findings led to recommendations for future implementations of managed CCE services in National Health Service (NHS) Scotland that could also apply more widely (United Kingdom and beyond) and at a greater scale (with more patients in more contexts). These include promoting CCE with, for, and among clinical teams to ensure adoption and success; capturing and understanding reasons why patients do and do not opt for CCE; providing clear information in a variety of appropriate ways to patients (eg, around the importance of bowel preparation instructions); improving the bowel preparation (this is not specific to CCE alone); providing flexible options for issuing and returning the kit (eg, dropping off at a pharmacy); and embedding formative evaluation within the service itself (eg, capturing patient-reported experiences via surveys in the information pack when the equipment is returned).